Trace metals (Pb, Cu and Cd) deposition in sediment at Kong Kong Laut, Johor and Sungai Kerang, Perak - Khalid, Sara Azuana Khalidah; Zapar, Nurul Naqibah; Mohamat Yusuff, Ferdaus; Mohamed, Khairul Nizam; Mohd Kusin, Faradiella; Aris, Ahmad Zaharin; Zulkifli, Syaizwan Zahmir; Yahya, Salbiah (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
Availability of cockle at Kong Kong Laut had driven Koperasi Kampung Sungai Latoh KongKong Masai Berhad to start cockle farming. However due to lack of knowledge on environmental assessment and cockle cultivation method that can produce a maximum size quality of cockle, collaboration between industrial partner and Universiti Putra Malaysia (UPM) had been made through Knowledge Transfer Programme (KTP) in order to overcome this gap. This study focused on environmental assessment of selected trace metals which are Lead (Pb), Copper (Cu) and Cadmium (Cd) deposition of sediment at Kong Kong Laut Masai Johor and Sungai Kerang Perak. Sungai Kerang in this study act as a reference area as it is well- established for cockle farming. Sample of sediments was collected at the end of June 2014 in Kong Kong Laut, Masai, Johor and early on September 2014 in Sungai Kerang Perak. Metal elements were detected by using atomic absorption spectrophotometer. Data were analyzed by using independent t-test and shown that there are no significant differences of trace metals between both study areas. Results show mean concentration of Pb (Kong Kong: 16.401 ± 0.027 μg g-1; Sungai Kerang: 12.851 ± 0.113 μg g-1) at both study areas is higher than the mean concentration of Cu (Kong Kong: 11.051 ± 0.015 μg g-1; Sungai Kerang: 11.651 ± 0.031 μg g-1) and Cd (Kong Kong: 2.300 ± 0.007 μg g-1; Sungai Kerang: 2.550 ± 0.007 μg g-1) respectively. In comparison with ISQGs, level of Pb and Cu in sediment at both study areas are significantly lower than the low standard level of Hong Kong Sediment Quality Guidelines (Low- HKSQG); Pb (75 μg g-1), Cu (65 μg g-1). In contrast, Cd level is higher than the Low- HKSQG; Cd (1.5 μg g-1) but still below the high standard of Hong Kong Sediment Quality Guideline (High- HKSQG); Cd (4 μg g-1). Concentration of Cd was higher than HK SQGs is due to anthropogenic activities. Data obtained had been share with industrial partner in knowledge transfer and river conservation programme with hoped that these activities will be able to impart knowledge on how to improve environmental pollution in river for cockle cultivation.